Well-defined polyacrylamides with AIE properties via rapid Cu-mediated living radical polymerization in aqueous solution: thermoresponsive nanoparticles for bioimaging. Issue 1 (10th December 2021) - Ma, Congkai; Han, Ting; Niu, Niu; Al-Shok, Lucas; Efstathiou, Spyridon; Lester, Daniel; Huband, Steven; Haddleton, David
Abstract : There is a requirement for the development of methods for the preparation of well-controlled polymers with aggregation-induced emission (AIE) properties. Abstract : There is a requirement for the development of methods for the preparation of well-controlled polymers with aggregation-induced emission (AIE) properties. This requirement directed this current work towards a robust synthetic route, which would be applicable for preparation in water and the presence of many types of functional groups. Herein, aqueous Cu-mediated living radical polymerization (LRP) has been optimized to provide facile and rapid access to a diverse range of water-soluble AIE polymers at sub-ambient temperatures. Homo-, block and statistical copolymerization all proceeded to a near full monomer conversion (≥99%) within 1 or 2 h and exhibited narrow dispersity, even when DP was targeted up to 1000. This excellent control associated with this polymerisation technique and the high-end group fidelity achieved were further demonstrated by linear first order kinetics and successful in situ block copolymerization, respectively. Fine-tuning the monomer sequence and composition of poly( N -isopropylacrylamide) (PNIPAM) copolymers allows for different lower critical solution temperature (LCST) and fluorescent thermoresponsive nanoparticles, which spontaneously self-assembled to varying sizes in water as determined by a combination of techniques (DLS, SAXS and TEM). Additionally, the fluorescence intensity was demonstrated to depend on the polymer concentration, architecture of the side chains and temperature. Particularly, PNIPAM-containing polymers were resistant to reduction in thermo-induced emission. The good biocompatibility, photostability and high specificity make them promising candidates as lysosome-specific probes for application in bioimaging.